2021
DOI: 10.3390/ani11030627
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Transcriptome Profile between Iberian Pig Varieties Provides New Insights into Their Distinct Fat Deposition and Fatty Acids Content

Abstract: The high deposition of intramuscular fat and the content of oleic fatty acid are characteristic of the Iberian pig. These two parameters present great variability and are differentiated amongst the varieties that make up the Iberian pig population. Although previous studies generated evidence for causal genes and polymorphisms associated to the adipogenic potential of the Iberian pig, there is little information about how genetic expression influences this trait’s variability. The aim of this study was to anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 45 publications
(70 reference statements)
0
8
0
Order By: Relevance
“…Clemente et al (2006) and Dieguez (2000) [ 39 , 40 ] studied the genetic origin of the Iberian strains, and several authors [ 14 , 15 , 16 , 41 ] compared fat deposition and lipid metabolism among different strains within the Iberian breed, with some differences in their findings that were not fully coherent. Additionally, differences in the expression of genes related to lipid metabolism have previously been studied comparing pure Iberian vs. Duroc x Iberian crossbreeds [ 23 ], pure Iberian vs. pure Duroc [ 22 ], and among Iberian strains and their crossbreeds [ 24 ]. In the present study, not only genotype, but also feeding system significantly affected fat deposition and fatty acid profiles, as also reported by Daza et al (2007), Martins et al (2015), and Rey et al (2006) [ 4 , 21 , 42 ], as well as the expression of relevant genes involved in muscle lipogenic processes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clemente et al (2006) and Dieguez (2000) [ 39 , 40 ] studied the genetic origin of the Iberian strains, and several authors [ 14 , 15 , 16 , 41 ] compared fat deposition and lipid metabolism among different strains within the Iberian breed, with some differences in their findings that were not fully coherent. Additionally, differences in the expression of genes related to lipid metabolism have previously been studied comparing pure Iberian vs. Duroc x Iberian crossbreeds [ 23 ], pure Iberian vs. pure Duroc [ 22 ], and among Iberian strains and their crossbreeds [ 24 ]. In the present study, not only genotype, but also feeding system significantly affected fat deposition and fatty acid profiles, as also reported by Daza et al (2007), Martins et al (2015), and Rey et al (2006) [ 4 , 21 , 42 ], as well as the expression of relevant genes involved in muscle lipogenic processes.…”
Section: Discussionmentioning
confidence: 99%
“…The SCD (stearoyl-CoA desaturase) gene, responsible for the biosynthesis of MUFA, was upregulated in Iberian pigs when compared with pure Duroc pigs [ 22 ], and also when compared with the Duroc x Iberian F1 genotype [ 23 ]. Moreover, when comparing Iberian R and T strains and their diallelic crosses, Villaplana-Velasco et al (2021) [ 24 ] found that the R genotypes had the highest content of PUFA and SFA because the genes related to fatty acid catabolism were downregulated in this genotype.…”
Section: Introductionmentioning
confidence: 99%
“…Second, PPARD is recognized as an important gene associated with fat deposition traits in gene and gene expression layers [17,43,44], which was detected in our study in QTL on SSC7 and annotated by all the databases. Third, SLC27A1 was another detected important genes that showed multiple evidence associated with fat deposition [45][46][47]. In addition, we identified seven promising candidate genes, PHLPP1, NUDT3, ILRUN, RELCH, KCNQ5, ITPR3, and U3.…”
Section: Discussionmentioning
confidence: 90%
“…FABP4 exists primarily in adipose tissue, which is vital for lipid metabolism in adipocytes ( Falcao-Pires et al, 2012 ). FABP5, a lipid chaperone, regulates fatty acid transport, metabolism, and storage ( Liu et al, 2018 ; Villaplana-Velasco et al, 2021 ; Xing et al, 2021 ). FABPs are candidate genes that regulate porcine fat deposition in many other studies.…”
Section: Discussionmentioning
confidence: 99%